Maximum power point tracking in grid connected PV system using a novel fuzzy logic controller - Subiyanto; Mohamed, A.; Hannan, M.A. (2009 IEEE Student Conference on Research and Development, 2009)
This paper presents modeling and simulation of a grid connected photovoltaic (PV) system with maximum power point tracking (MPPT) using a novel fuzzy logic controller (FLC). The system composed of a PV array, boost converter with MPPT and a three phase inverter connected to utility grid. The MPPT is based on fuzzy logic to control IGBT switch of the boost converter. The performance of the proposed FLC for MPPT is evaluated by simulation and the results show that the FLC is faster and more stable in finding the maximum power point than the conventional perturbation and observation method. The performance of the PV system subjected to load variation and islanding is also investigated.